Comparison of the 2010 and 2020 World Health Organization guidelines on physical activity in patients with percutaneous coronary interventions early after hospital discharge. (11th May 2022) - Eser, P; Gonzalez-Jaramillo, N; Weber, S; Femiano, R; Werner, C; Casanova, F; Bano, A; Franco, OH; Wilhelm, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Swiss heart foundation Background: Physical activity (PA) is inversely associated with mortality and adverse outcome in patients with cardiovascular disease, and can be objectively measured by accelerometry. In 2020, the World Health Organization (WHO) has updated their recommendations on PA for adults including those with chronic conditions, omitting the 10 min bout criterion.[1] The aim of this study was to determine the proportions of cardiac patients immediately after hospital discharge from percutaneous coronary interventions (PCI) who fulfil the old [2] and updated WHO PA criteria, and compare the results with established step-based cut-off values. Methods: Patients after PCI for acute or chronic coronary syndrome with a maximal age of 80 and eligible for ambulatory cardiac rehabilitation were recruited for this observational single centre study. They were provided with a wrist-worn tri-axial accelerometer without display that recorded movement data starting from the day following hospital discharge for the subsequent 18 days. Acceleration data was analysed with the widely used free GGIR package. The proportions of patients fulfilling recommendations for moderate to vigorous PA (MVPA) were determined according to the 2010 and 2020 WHO guidelines as well as 7, 500 [3] and 10, 000 steps.[4] Results: 159 patients (41%) participated in this study. Data from 135 patients (85%), who had at least 7 days of ≥12 h wear-time were included in the analyses. Their median age was 62 (1st quartile 56, 3rd quartile 68), 22 (16%) were women, and 15 and 120 patients had a CCS and ACS, respectively. Their median wear time was 18 (16, 18) days. 102 (75.6%) had at least 30 min of MVPA on an average day and hence fulfilled the 2020 WHO guidelines. When MVPA was determined using the 2010 WHO guidelines, which only counted MVPA of bouts of at least 10 min, only 23 patients (17.8%) achieved at least 30 min of MVPA on an average day (Figure 1). 67.4% of our patients achieved ≥7, 500 steps/d and 71 patients (52.6%) performed ≥10, 000 steps/d. Conclusion: In cardiac patients early after PCI most of the MVPA was accumulated in bouts shorter than 10 min. Applying the 2010 and 2020 WHO PA criteria to objectively measured PA led to a fourfold discrepancy. The 7, 500 step cut-off corresponded with the 2020 WHO recommendations. Since achievement of intensity- or step-based cut-offs is greatly dependent on device type, wearing location, data sampling and analysis, it is currently poorly defined and not suited for patient classification and counselling. The clinical implication of this observation will be assessed in a cardiovascular outcome analysis.